Experience and perceptions regarding menopause among rural women: A cross-sectional hospital-based study in South Karnataka - Deepika Nagaraj; Naveen Ramesh; Divya Devraj; Marciya Umman; Anila K John; Avita Rose Johnson (Wolters Kluwer Medknow Publications, 2021)
Background: There is a culture of silence around menopause in India, more so among rural women. This study was conducted to assess the prevalence of menopausal symptoms, factors associated with the severity of menopausal symptoms, and perceptions regarding menopause among rural perimenopausal women. Methodology: A cross-sectional study was conducted at a rural hospital, among women aged 40 years or more, having experienced at least one menstrual cycle in the past 1 year. Structured interview schedule was administered to capture perceptions of menopause. Symptoms of menopause and severity were assessed using the Menopause Rating Scale (MRS) and participants screened for depression using patient health questionnaire-9. Results: Among 200 women, the prevalence of symptoms of menopause was 70%. Commonly reported symptoms were somatic symptoms: Joint/muscular pain, hot flushes, and psychological symptoms: Physical/mental exhaustion, anxiety. Median overall MRS score was low (4 [interquartile range = 1, 7]), pointing out to lesser severity. Significant association was found between MRS score and higher body mass index (P = 0.007), tobacco-chewing (P = 0.023), and depression (P < 0.001). Perception of menopause was generally positive, but we also documented some myths and misconceptions regarding menopause that indicate a need for health awareness in this population. Conclusion: This study found high prevalence but low severity of menopausal symptoms. Our findings point to a need for mitigating symptoms of menopause through diet, physical activity, tobacco cessation, and counseling for depression. Targeted interventions using community women's groups and village-level health workers are recommended to provide not only awareness regarding menopause but also an opportunity to screen for comorbidities with appropriate referrals.